2001
DOI: 10.1097/00007632-200101010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Quebec Classification of Whiplash-Associated Disorders

Abstract: The analyses of this study support the use of the Québec Classification of Whiplash-Associated Disorders as a prognostic tool for emergency department settings, and the authors propose a modification of the Classification using a subdivision of the Grade II category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
1
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 17 publications
1
87
1
11
Order By: Relevance
“…An example is Whiplash Associated Disorders (WAD), the myriad of signs and symptoms that result from a whiplash mechanism of injury [2], where patients are found to have ROM reduced by approximately 25% compared to asymptomatic populations [3,4]. ROM measurements have also demonstrated the potential for categorising patients who are at risk of a poor outcome following a whiplash injury [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…An example is Whiplash Associated Disorders (WAD), the myriad of signs and symptoms that result from a whiplash mechanism of injury [2], where patients are found to have ROM reduced by approximately 25% compared to asymptomatic populations [3,4]. ROM measurements have also demonstrated the potential for categorising patients who are at risk of a poor outcome following a whiplash injury [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Grades I and II which include only soft tissue injuries represent almost 90% of whiplash injuries and represent what is usually associated with the term WAD [22]. The incidence of WAD has increased rapidly during the last 20 years and is now estimated to be approximately 4 per 1,000 persons in Western countries [2,11,14,26].…”
Section: Introductionmentioning
confidence: 99%
“…However, Berglund et al [2] concluded in their prospective study that cases without symptoms after rear end collisions (i.e., WAD grade 0) do not have an increased risk of developing chronic WAD. There was a high number of cases missing in the study by Hartling et al [12], increasing from 12% at the 6 month follow-up to 25% at 24 months.…”
Section: Discussionmentioning
confidence: 79%
“…All cases were examined and treated by the same doctor (J.K.) in a standardized fashion. In a report by Hartling et al [12] on 380 cases from two emergency departments in Ontario, Canada it was concluded that the Quebec classification was useful for predicting chronic WAD. In their study, the outcome was a non-validated pain score questionnaire based on a telephone interviews.…”
Section: Discussionmentioning
confidence: 99%